Establecimiento de parcelas de escorrentía para la estimación de la erosión hídrica generada por la actividad ganadera en la microcuenca del Río Santa Rosa, Guanacaste - Masís-Solano, Jonathan (Instituto Tecnológico de Costa Rica, 2017)
With the purpose of generating information for the establishment of a management plan of the erosion problem that triggers the filling of the reservoirs that form part of the Arenal-Corobicí-Sandillal Generation Center, a series of experiments were developed to determine the contribution of Sediments generated by livestock activity, as well as evaluate the effect of slope, resistance to penetration, degree of infiltration and precipitation. Monitoring plots were established in two types of land uses, extensive and extensive cattle ranching, on two altitudinal floors, in the Santa Rosa river basin, Guanacaste, Costa Rica. For the estimation of erosion, the methodology of installation of geomembranes called "silt fence" was used, performing monitoring every 15 days. A soil loss of 16 kg / ha was estimated during the evaluation period from January 18 to July 28, analyzing the effect of slope, increasing slope increased erosion rate, topographies evaluated between 0-15% They obtained 3kg / ha, the conditions between 15-30% presented a loss of 12kg / ha, the slopes of 30-45% reached 28kg and in the case of slopes between 45-60% erosion was 123kg / ha. The conditions of use, extensive and intensive cattle ranching did not present differences for the lost soil variable, likewise, there are no differences between the livestock uses in the high and low microbasins for the aforementioned variable. The relationship of the resistance to penetration with the variable percentage of clays present in the studied soils and their apparent density does not allow to explain if there is a relation between the variables and the degree of compaction in the different uses of the soil, because the estimated correlations Between the different variables are very low. On the other hand, the phenomenon that explains the little erosion generated by the cattle ranch in the Santa Rosa river microbasin is the capacity of infiltration of the soils because the maximum precipitation during each event was less than the capacity of infiltration, so that Decreases runoff. Phenomenon aided by the perennial coverage of the pasture species found in the study area.
Trabajo Final de Graduación (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2017.
Keywords: Ganadería; Erosión; Precipitación; Uso del suelo; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Agronomy